2018
DOI: 10.1139/cjb-2017-0104
|View full text |Cite|
|
Sign up to set email alerts
|

Breeding system and inbreeding depression in the rare orchid,Platanthera praeclara, in a fragmented grassland landscape

Abstract: An important consequence of self-compatibility in plants is that self-pollination can have deleterious effects on plant fitness due to inbreeding. We conducted a hand pollination experiment under field conditions to measure the magnitude of inbreeding depression associated with self-pollination in the rare western prairie fringed-orchid Platanthera praeclara Sheviak and Bowles. By comparing capsules and seeds resulting from cross versus self-pollination treatments, we determined that self-pollination reduces s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…The reduction in fitness associated with elevated homozygosity, known as inbreeding depression, is commonly seen in orchids (Juillet et al, 2007; Ortiz‐Barney & Ackerman, 1999; Sletvold et al, 2012). Several studies have shown a reduced seed production in selfed plants, including orchids (Sletvold et al, 2012), the genus Platanthera (Gregg, 1990; Nilsson, 1983; Patt et al, 1989; Travers et al, 2018), and more specifically this species (Wallace, 2003). However, inbreeding depression can also express itself in other demographic life stages including germination, seedling performance, and survival (Juillet et al, 2007; Sletvold et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in fitness associated with elevated homozygosity, known as inbreeding depression, is commonly seen in orchids (Juillet et al, 2007; Ortiz‐Barney & Ackerman, 1999; Sletvold et al, 2012). Several studies have shown a reduced seed production in selfed plants, including orchids (Sletvold et al, 2012), the genus Platanthera (Gregg, 1990; Nilsson, 1983; Patt et al, 1989; Travers et al, 2018), and more specifically this species (Wallace, 2003). However, inbreeding depression can also express itself in other demographic life stages including germination, seedling performance, and survival (Juillet et al, 2007; Sletvold et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This mode may be beneficial to enhance the adaptability of D. wangliangii to adverse environments, such as drought, short florescence, and pollinator‐scarce conditions (Abdel‐Ghani, Parzies, Omary, & Geiger, ; Miranda & Vieira, ). In addition, cleistogamy reduces the threat of genetic contamination and gene flow through crossing with other plants of the same species (Faisal et al, ; Travers, Anderson, Vitt, & Harris, ; Zou et al, ). Outcrossing has a selective advantage, such as maintaining high genetic diversity and avoiding sibling competition (Antlfinger, ; Cozzolino & Widmer, ; Culley & Klooster, ; Schmitt, Ehrhardt, & Swartz, ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, cleistogamy is favored under adverse and stressful conditions (e.g., scarce-pollinator, water deficiencies), which are unsuitable for cross-pollination (Schemske, 1978;Solbrig, 1976 (Faisal et al, 2018;Travers, Anderson, Vitt, & Harris, 2018;Zou et al, 2018). Outcrossing has a selective advantage, such as maintaining high genetic diversity and avoiding sibling competition (Antlfinger, 1986;Cozzolino & Widmer, 2005;Culley & Klooster, 2007;Schmitt, Ehrhardt, & Swartz, 1985).…”
Section: Dendrobium Dixanthummentioning
confidence: 99%
“…The most TA B L E 2 Associated floral visitor and pollinator information for various Platanthera species obtained from literature sources. (1971), Dobson (1988), Vogt (1990), Boland (1993), Catling and Catling (1991), Larson (1992) few studies that reported the amount of nectar present, it seems that nectar quantity is highly variable, with reports of 2-4 mm in the spur (Nilsson, 1978) and 3.3 mg (Stpiczynska, 2001) for P. chlorantha, 20 μL (Travers et al, 2018) for P. praeclara, and 0.1 μL (Patt et al, 1989) for P. stricta. Platanthera nectar typically has a high sugar concentration, and sucrose concentrations are much higher than fructose or glucose, according to the few sources available.…”
Section: Linking Pollinator Needs and Behavior To Orchid Reproductive...mentioning
confidence: 99%